Efektifkah Pemberantasan Korupsi di Lingkungan Pemerintah dengan memperbaharui Sistem Remunerasi? - Yudiantarti Safitri (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2008)
National development is an essential pillar of human resources, if itâ€™s quality is substandard then the national development will also be substandard. Civil servants are a key component to the national development thus the government must devote more resources in order to maintain top quality performance. It is a general consensus that low Civil Servants wages is the root cause of corruption that exist today in the government. For this reasons in late 2007 the following bureaucratic reformation began in the treasury department: organizational restructuring; streamlining business processes; improving human resource management; and overhauling remuneration. According to ordinance Number 48 year 1999 â€œgovernment employee salaries are based upon merit as define in section 7 number (1): All government official have the right to adequate compensation based on their position and responsibilities; and number (2): the salary must both motivate the employees and provide them with financial prosperity.â€ One goal of the bureaucratic reformation is to fix the remunerasi system; plus the hopes are to improve civil servant motivation and performance. But the question is whether the remuneration system can eliminate corruption from the governmental environment.